How to manage a late diagnosed Hirschsprung's disease - Mohamed Ouladsaiad (Wolters Kluwer Medknow Publications, 2016)
Background: How to manage a late diagnosed Hirschsprung's disease (HD) and how to avoid calibre discrepancy? Subjects and Methods: A retrospective study of all patients diagnosed with HD over 2 years in our hospital from January 2009 to December 2012. Data were analysed for clinical presentations, investigations, surgical procedures and post-operative outcome. Results: Fifteen patients, operated by one single surgeon, were included in this study. The mean age was 6 years (2-16 years). Patients had an ultra-short segment type in 4 cases, rectosigmoid type in 9 cases and descending colonic aganglionosis in 2 cases. Rectal wash out was effective in 12 patients. A blowhole transverse colostomy was performed in 2 patients. Twelve patients underwent one single stage endorectal pull-through. Anastomosis incongruence was avoided by a plication procedure never described before. The assessment of post-operative outcomes by the paediatric incontinence and constipation scoring system revealed a normal continence function in all our patients, but 3 patients suffered from soiling secondary to constipation. Conclusion: One single stage pull-through can be safe and effective in children with late diagnosed HD. Routine rectal washout is a good way to prepare the colon. In some cases, blowhole colostomy can be an option. Anastomosis incongruence is a challenge; we describe a plication procedure to avoid it.